Effect of cold sintering process (CSP) on the electro-chemo-mechanical properties of Gd-doped ceria (GDC). Issue 15 (December 2020) - Kabir, Ahsanul; Espineira-Cachaza, Martin; Fiordaliso, Elisabetta Maria; Ke, Daoyao; Grasso, Salvatore; Merle, Benoit; Esposito, Vincenzo
Abstract: In this report, the effect of the cold sintering process (CSP) on the electro-chemo-mechanical properties of 10 mol% Gd-doped ceria (GDC) is investigated. High purity nanoscale GDC powder is sintered via a cold sintering process (CSP) in pure water followed by post-annealing at 1000 °C. The resultant ceramics exhibits high relative density (∼90 %) with a fine grain size of ∼100 nm. This sample illustrates comparable electrochemical properties at intermediate-high temperatures and electromechanical properties at room temperature to the material prepared via conventional firing, i.e., sintering in the air at 1450 °C. Moreover, a large creep constant, as well as a low elastic modulus and hardness, are also observed in the CSP sample.